Imaging moiré deformation and dynamics in twisted bilayer graphene - Tobias A. de Jong; Tjerk Benschop; Xingchen Chen; Eugene E. Krasovskii; Michiel J. A. de Dood; Rudolf M. Tromp; Milan P. Allan; Sense Jan van der Molen (Nature Communications, 2022)
Local variations of twist angle and strain in twisted bilayer graphene (TBG) can produce relevant changes in the electronic properties of the system. Here, high-resolution low energy electron microscopy is used to characterize the spatial and temporal deformations of moiré patterns in TBG at high temperatures, showing the stability of these structures up to 600 ∘C.